The design of Gamelan (Saron Barong) Playing Machine by using Peripheral Interface Controller (PIC) 16F84A / Mohd Faizol Che Mat - Che Mat, Mohd Faizol (2007)
This project proposes the design of Gamela Playing Machine via the usage of microntrolller namely PI 16F84A in circuitry system. The program build by using MPLAB software and PIC StartPlus programmer.